Encapsulating deontic and branching time specifications - Castro, Pablo Francisco (2012)
In this paper, we investigate formal mechanisms to enable designers to decompose specifications (stated in a given logic) into several interacting components in such a way that the composition of these components preserves their encapsulation and internal non-determinism. The preservation of encapsulation (or locality) enables a modular form of reasoning over specifications, while the conservation of the internal non-determinism is important to guarantee that the branching time properties of components are not lost when the entire system is obtained. The basic ideas come from the work of Fiadeiro and Maibaum where notions from category theory are used to structure logical specifications. As the work of Fiadeiro and Maibaum is stated in a linear temporal logic, here we investigate how to extend these notions to a branching time logic, which can be used to reason about systems where non-determinism is present. To illustrate the practical applications of these ideas, we introduce deontic operators in our logic and we show that the modularization of specifications also allows designers to maintain the encapsulation of deontic prescriptions; this is in particular useful to reason about fault-tolerant systems, as we demonstrate with a small example.